Anaerobutyricum hallii promotes the functional depletion of a food carcinogen in diverse healthy fecal microbiota - Ramirez Garcia, Alejandro; Greppi, Anna; Constancias, Florentin; Ruscheweyh, Hans-Joachim; Gasser, Julie; Hurley, Katherine; Sturla, Shana J.; Schwab, Clarissa; Lacroix, Christophe (Frontiers in Microbiomes, 2023)
Anaerobutyricum hallii is a human gut commensal that transforms the heterocyclic amine 2amino-1-methyl-6-phenylimidazo [4,5-b] pyridine (PhIP), a carcinogen from cooked meat. The mechanism involves microbial production of acrolein from glycerol, and its conjugation with PhIP, thus blocking its mutagenic potential. A potential cancer prevention strategy could therefore involve supplementing complex human microbial communities with metabolically competent bacteria such as A. hallii that can deplete PhIP. However, it has not been established how the proportion of A. hallii in diverse healthy human gut microbial communities relates to functional capacity for PhIP transformation, and moreover, how supplementing microbiomes with A. hallii affects this function. Here, shotgun metagonomics was used to study taxonomic profiling, abundance of gdh harboring taxa, and proportion of resident A. hallii and reconstruction of A. hallii populations genomes in the fecal sample of 20 healthy young adult donors. Furthermore, the influence of supplementing 10 6 cells/mL of A. hallii DSM 3353 to diluted fecal microbiota was characterized. Six microbiota were assigned to Bacteroides, nine to Prevotella and five to Ruminococcus by enterotype-associated clustering. Total gdh copies in the 20 fecal microbiota expressed per 10 10 bacterial cells ranged between 1.32x10 8 and 1.15 x10 9 . 18 out of 20 donors were dominated by A. hallii, representing between 33% and 94% of the total gdh relative abundance of the samples. Microbiota with low A. hallii abundance (relative abundance <1%) transformed less PhIP, as compared with the microbiota with high A. hallii abundance (relative abundance >1%). Furthermore, supplementing the low A. hallii abundant microbiota with glycerol significantly increased the PhIP transformation capacity after 6 h, while reducing total SCFA levels likely due to acrolein production. While acetate decreased in all microbiota with glycerol and with the combination of glycerol and A. hallii, for most of the microbiomes butyrate production increased over time. Thus, for a significant number of diverse healthy human fecal microbiomes, and especially when they have little of the taxa to start with, supplementing A. hallii increases PhIP transformation. These findings suggest the need to test in vivo whether supplementing microbiomes with A. hallii reduces PhIP exposure.